2008
DOI: 10.1016/j.jvs.2007.08.053
|View full text |Cite
|
Sign up to set email alerts
|

Association of abdominal aortic aneurysm, horseshoe kidneys, and left-sided inferior vena cava: Report of two cases

Abstract: Surgery for abdominal aortic aneurysm may be challenging when rare renal or venous anomalies are present. This article reports two similar cases of aortic abdominal aneurysm associated with horseshoe kidney and left-sided inferior vena cava treated with a transperitoneal approach. Preoperative knowledge of the anatomic situation enabled appropriate aneurysm repair. Operative strategy is discussed. This report describes an uncommon venous vascular malformation complex and stresses the importance of computed tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Azygos continuation of IVC was present in only 0.1% on contrast-enhanced CT. 23 The IVC is formed from a complex network of the following 3 parallel pairs of embryological veins: the posterior cardinal veins, the subcardinal veins, and the supracardinal veins ( Figure 5). 9,24 These veins anastomose to themselves, and later partially regress. Faults in this development may result in 5 types of anomalies of the IVC and left renal vein, including double IVC, persistence of the normally involuted left supracardinal vein, pre-aortic confluence of the iliac veins, left IVC, and a circum-aortic renal vein collar that duplicates the left renal veins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Azygos continuation of IVC was present in only 0.1% on contrast-enhanced CT. 23 The IVC is formed from a complex network of the following 3 parallel pairs of embryological veins: the posterior cardinal veins, the subcardinal veins, and the supracardinal veins ( Figure 5). 9,24 These veins anastomose to themselves, and later partially regress. Faults in this development may result in 5 types of anomalies of the IVC and left renal vein, including double IVC, persistence of the normally involuted left supracardinal vein, pre-aortic confluence of the iliac veins, left IVC, and a circum-aortic renal vein collar that duplicates the left renal veins.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is plausible that horseshoe kidney and left IVC, or the anomalous involution of the right surpacardinal vein, are the consequence of a shared disturbed signal during the development of these retroperitoneal structures. 9 Another explanation could be that a horseshoe kidney and its related failure of cephalic ascent and abdominal rotation may have a direct effect on the locoregional development of the complex cardinal venous network. Compression of segments of the cardinal veins by the abnormal kidney mass could induce their regression and involution.…”
Section: Discussionmentioning
confidence: 99%
“…3 Because embryogenesis of the renal parenchyma and its venous drainage in the IVC occur simultaneously during gestational weeks 4-10, it is plausible that horseshoe kidneys and anomalous IVCs are consequences of a shared disturbed signal that occurs during the development of these retroperitoneal structures. 6 Glodry et al reported a case of a persistent left SVC with a fusion anomaly of the kidney, but it is unclear if the anomaly was horseshoe kidney or crossed fused ectopia. 13 Two other cases of an anomalous SVC with horseshoe kidney have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…8 Horseshoe kidney is associated with IVC anomalies because their development occurs around the same gestational period. 6 The SVC and IVC differentiate around gestational weeks 4-10. The SVC derives from the anterior and common cardinal veins, whereas the IVC derives from the supra-and subcardinal veins (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…11). There has been described an AAA with horseshoe kidney and left-sided inferior vena cava, resolved with open surgery (Evers et al, 2007;Giglia & Thompson 2004;Radermecker et al, 2008). Fig.…”
Section: Left-sided Inferior Vena Cavamentioning
confidence: 99%